Comparison between 2D and 3D ERT inversion for engineering site investigations – a case study from Oslo Harbour. Issue 2 (1st December 2016) - Lysdahl, Asgeir Kydland; Bazin, Sara; Christensen, Craig; Ahrens, Sven; Günther, Thomas; Pfaffhuber, Andreas A.
ABSTRACT: Excavation and piling works related to seafront development in Oslo's historic harbour area need to mitigate the risk of damaging buried archaeological objects. In the Bjørvika harbour in Oslo, Norway, electrical resistivity tomography was performed to detect structures with potential archaeological value. A 2.5 dataset consisting of four equally spaced parallel lines was collected, trimmed, and systematically processed with both 2D and 3D inversion routines. The results were in good agreement with known underground features, and for the present dataset, an iteratively reweighted least squares 2D inversion was clearly preferable over a 3D inversion. This conclusion is based on differences in model resolution, data processing costs, and the value of the final product for engineering decision‐making.